Dons back call to bring back ISA - Malay, Mail (Malay Mail, 2014)
THE Internal Security Act (ISA) should be brought back, if necessary under a new name, as there appears to be widespread public support for a strong preventive law.Universiti Utara Malaysia's College of Law and International Relations dean Prof Dr Ahmad Marthada Mohamed said such a preventive law was necessary and timely.